Implementasi strategi humas berbasis kemitraan dalam membangun citra sekolah: Studi di MTs Muhammadiyah 1 Malang - Nuur’Ainii, Aanisah Jahroo’ Fitriyyah (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of partnership-based public relations strategies in building the school image at MTs Muhammadiyah 1 Malang. Using a qualitative approach with observation, interviews, and documentation techniques, this research explores how the public relations unit functions in managing communication and developing collaborative relationships with various stakeholders. The findings indicate that the public relations team has carried out its role through activity publications, the use of digital media, and coordination with parents, the community, and external partners. These efforts contribute to strengthening information transparency and enhancing the school’s positive image. However, the effectiveness of the implemented strategies is hindered by several challenges, including limited human resources, insufficient documentation and evaluation, and the absence of standardized visual identity in digital publications. These limitations lead to inconsistent communication and weaken the school’s branding efforts. The study recommends strengthening PR human resource capacity, establishing a structured documentation system, and developing standardized digital publication guidelines to ensure more effective and sustainable partnership-based public relations strategies.